On Lacunary Ideal Convergence in Random n-Normed Space. (18th February 2013) - Yamancı, U.; Gürdal, M.
Abstract : We introduce the notions of lacunary ℐ -convergence and lacunary ℐ -Cauchy in the topology induced by random n -normed spaces and prove some important results.